Effects of a Dynamic Chair on Chair Seat Motion and Trunk Muscle Activity during Office Tasks and Task Transitions - Nüesch, Corina (Int J Environ Res Public Health, 2018)
Employing dynamic office chairs might increase the physical (micro-) activity during prolonged office sitting. We investigated whether a dynamic BioSwing(®) chair increases chair sway and alters trunk muscle activation. Twenty-six healthy young adults performed four office tasks (reading, calling, typing, hand writing) and transitions between these tasks while sitting on a dynamic and on a static office chair. For all task-transitions, chair sway was higher in the dynamic condition (p < 0.05). Muscle activation changes were small with lower mean activity of the left obliquus internus during hand writing (p = 0.07), lower mean activity of the right erector spinae during the task-transition calling to hand writing (p = 0.036), and higher mean activity of the left erector spinae during the task-transition reading to calling (p = 0.07) on the dynamic chair. These results indicate that an increased BioSwing(®) chair sway only selectively alters trunk muscle activation. Adjustments of chair properties (i.e., swinging elements, foot positioning) are recommended.